Criminal Responsibilities of Criminal Trafficking in PerCriminal Responsibilities of Criminal Trafficking in Persons with Mail-Order Bride Mode Between China and Indonesiasons with Mail-Order Bride Mode Between China and Indonesia - Reine Rofiana; Muhyi Mohas; Belardo Prasetya Mega Jaya; Nuryati Solapari; Shofia Khairunnisa (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2022)
Abstract: This article discusses legal provisions regarding the criminal act of trafficking in persons between Indonesia and China with the mail-order bride mode, which has recently occurred in various regions in Indonesia, and the criminal responsibility of the perpetrators of the trafficking in persons. The primary sources of this research are Law No. 21 of 2007 on the Eradication of Human Trafficking, the Criminal Law of the People’s Republic of China, Law No. 13 of 2017 concerning the Ratification of the Agreement between the Republic of Indonesia and the People’s Republic of China regarding Extradition, and the results of interviews with various party. The secondary sources come from scientific works that study or are related to the object of this research. Using juridical-empirical approach, this study results indicate that the criminal act of trafficking in persons with the order mode of the bride and groom between men with Chinese citizenship and women with Indonesian citizenship was committed by several parties, including Indonesian agents, Chinese agents, mail-order bride service users, and intermediary parties (makcomblang). The perpetrators of the crime of trafficking persons who are in Indonesia can be subject to criminal sanctions as stipulated in Law No. 21 of 2007 on the Eradication of Human Trafficking. Meanwhile, perpetrators who are domiciled in China can be subject to criminal sanctions through extradition based on an extradition agreement between China and Indonesia (July 1, 2009) which has been ratified by Law No. 13 of 2017 concerning the Ratification of the Agreement between the Republic of Indonesia and the People’s Republic of China regarding Extradition. Abstrak: Artikel ini mengkaji ketentuan hukum tentang tindak pidana perdagangan orang antara Indonesia dan Cina dengan modus pengantin pesanan yang akhir-akhir ini banyak terjadi di berbagai daerah di Indonesia dan  pertanggungjawaban pidana para pelaku tindak pidana perdagangan orang tersebut. Sumber utama penelitian ini adalah Undang-Undang Nomor 21 Tahun 2007 tentang Tindak Pidana Perdagangan Orang (TPPO), Criminal Law of the People’s Republic of China, Undang-Undang Nomor 13 Tahun 2017 tentang Pengesahan Persetujuan antara Republik Indonesia dengan Republik Rakyat Cina, dan hasil wawancara dengan berbagai pihak. Adapun sumber sekundernya berasal dari karya-karya ilmiah yang mengkaji atau berkaitan dengan objek penelitian ini. Menggunakan pendekatan yuridis-empiris, penelitian ini menemukan bahwa tindak pidana perdagangan orang dengan modus pengantin pesanan antara laki-laki berkewarganegaraan Cina dengan perempuan berkewarganegaraan Indonesia dilakukan oleh beberapa pihak, yang meliputi agen Indonesia, agen Cina, pengguna jasa pengantin pesanan, dan pihak perantara (makcomblang). Para pelaku tindak pidana perdagangan orang yang berada di Indonesia ini dapat dikenai sanksi pidana sebagaimana diatur dalam Undang-Undang Nomor 21 tahun 2007 tentang Pemberantasan Tindak Pidana Perdagangan Orang. Sementara para pelaku yang berkedudukan di negara Cina dapat dikenai sanksi pidana melalui pemberlakuan ekstradisi berdasarkan persetujuan ekstradisi antara Cina dan Indonesia (1 Juli 2009) dan telah disahkan dengan Undang-Undang Nomor 13 Tahun 2017 tentang Pengesahan Persetujuan antara Republik Indonesia dengan Republik Rakyat Cina.